Ventral hippocampal NMDA receptors mediate the effects of nicotine on stress-induced anxiety/exploratory behaviors in rats. (29th May 2022) - Farzamfard, Parinaz; Rezayof, Ameneh; Alijanpour, Sakineh
Graphical abstract: Highlights: Acute stress exposure induced anxiogenic-like effects. Nicotine administration inhibited stress-induced anxiogenic-like behaviors. Intra-VH microinjection of NMDA potentiated the nicotine response. Intra-VH microinjection of D-AP5 reversed the effect of NMDA on nicotine. Abstract: Brief exposure to stress increases the tendency to drug abuse, especially cigarette smoking. It seems that nicotine abuse alleviates some psychological and physiological stress symptoms. The present study investigated the effect of nicotine administration on stress-induced anxiety-like behavior in adult male Wistar rats. Also, the possible role of the ventral hippocampal (VH) glutamatergic NMDA receptors was examined in the stress-induced anxiety-like behavior under nicotine administration. The anxiogenic-like effects of forced swimming stress (10 min) were shown by decreases in the head-dipping behavior, rearing, and locomotor activity in a hole-board task. Interestingly, the administration of the different doses of nicotine (0.075 and 0.1 mg/kg, i.p.) inhibited stress-induced anxiogenic-like behaviors. Bilateral microinjection of NMDA (0.1 µg/rat) into the VH potentiated the response of an ineffective dose of nicotine (0.05 mg/kg, i.p.) on stress-induced anxiety-like behavior. The microinjection of D-AP5 (1.5 and 2 µg/rat) into the VH inhibited the response of an effective dose of nicotine (0.1 mg/kg, i.p.) on anxiety-like behavior induced by acute stress. Intra-VH microinjection of D-AP5 reversed the potentiating effect of NMDA on nicotine response. Intra-VH microinjection of NMDA or D-AP5 by itself did not affect stress-induced anxiety-like behavior. Taken together, we can conclude that nicotine inhibited stress-induced anxiogenic-like behaviors, possibly via the ventral hippocampal NMDA receptors mechanism.